Comparing biobehavioral profiles across two social stress paradigms in children with and without autism spectrum disorders - Corbett, Blythe A (BioMed Central, 2012)
BACKGROUND: Autism spectrum disorders (ASD) are defined by impairment in reciprocal social interaction and flexible adaptation to the environment. This study compared physiological stress in children with and without ASD exposed to two social stress protocols. We hypothesized that the ASD group would show heightened initial and enduring cortisol levels to the social stressors, which would be moderated by age and intelligence. METHODS: Twenty-seven children with ASD and 32 with typical development (TYP) completed a standardized social-evaluative performance task and a validated paradigm of social play with peers. Physiological stress was measured by salivary cortisol at nine time points. Statistical approaches included repeated-measures linear mixed models and correlation analyses. RESULTS: The average cortisol level of both groups during initial exposure to social situations was significantly greater than baseline levels (ASD, P = 0.018; TYP, P = 0.006). Stress responsivity was significantly different between the groups; the TYP group showed a significant reduction in cortisol over time (P = 0.023), whereas the ASD group maintained an elevated cortisol level (P >0.05). The ASD group evidenced greater variability in between-group, within-group and intra-individual analyses. Age was a positive moderator of stress for the ASD group (P = 0.047), whereas IQ was a negative moderator for the TYP group (P = 0.061). CONCLUSIONS: Initial stress to novel social scenarios is idiosyncratic and predictive of subsequent exposure. Amidst significant variability in cortisol, children with ASD show enhanced and sustained social stress that increases with age. Developmental and cognitive factors differentially moderate stress in children with ASD and TYP, respectively. A model of neuroendocrine reactivity is proposed.